Los peces inspiraron a investigadores para crear un blindaje (2021)
Inspired by nature and in order to achieve greater protection, flexibility and resistance against high-energy explosive charges, researchers from EAFIT and the company Tecnologías Marte created a novel synthetic material that resembles fish scales.